Pengaruh Penambahan Tepung Daun Kelor Terhadap Kandungan Nilai Gizi Cookies Kacang Hijau - Ataqwa, Krisjayanti; Wadli, Wadli; El Rizal Unzilatirrizqi D, Yan (Politeknik Negeri Ketapang, 2022)
Cookies are pastry products made from wheat flour which have a sweet taste and long shelf life cookies, to add good nutritional value by adding the formulation of mung bean flour and moringa leaf flour. The purpose of this study was to determine the effect of the formulation of mung bean cookies with Moringa leaf flour (Moringa oleifera L.) and on the organoleptic and nutritional values . This study used a completely randomized design (CRD) consisting of 5 treatments with concentrations of wheat flour: mung bean flour: moringa leaf flour (100 %: 0 %: 0 %), ( 50 % : 10 % : 40 %) , ( 50 % 35 % : 15 % ) , ( 50 % 25 % -25 % ) , and ( 50 % : 15 % : 35 % ) . The observed variables consisted of organoleptic properties : color , aroma , taste and texture and properties of water content , ash content , protein content , fat content and carbohydrate content , in order to conform to the sni standard for cookie quality . The data was processed using one way ANOVA test, and if it had a significant effect, it was continued to Duncan's follow-up test. The results showed the addition of Moringa leaf flour to cookies had a significant effect on the chemical properties of water content, ash content, protein content, fat content and carbohydrate content, and organoleptic properties. . The results selected by the panelists on the organoleptic test of cookies were in the P3 treatment with the composition of wheat flour: mung bean flour: ng Moringa leaves (50%: 25%: 25%) with organoleptic test value of taste = 5.93, color = = 5.80 , aroma 5,68 , texture = 6,28 and liking = 6,20 . With carbohydrate nutrient content of 46.87 % , nutritional content of water content of 4.15% , ash content of 3.61% , protein content of 9.35% and fat content of 36.02 %.